Nutritional strategies in ruminants: A lifetime approach. (February 2018) - McGrath, Joseph; Duval, Stéphane M.; Tamassia, Luis F.M.; Kindermann, Maik; Stemmler, René T.; de Gouvea, Vinícius N.; Acedo, Tiago S.; Immig, Irmgard; Williams, Scot N.; Celi, Pietro
Abstract: This review examines the role of nutritional strategies to improve lifetime performance in ruminants. Strategies to increase ruminants' productive longevity by means of nutritional interventions provide the opportunity not only to increase their lifetime performances and their welfare, but also to decrease their environmental impact. This paper will also address how such nutritional interventions can increase herd efficiency and farm profitability. The key competencies reviewed in this article are redox balance, skeletal development and health, nutrient utilization and sustainability, which includes rearing ruminants without antibiotics and methane mitigation. While the relationships between these areas are extremely complex, a multidisciplinary approach is needed to develop nutritional strategies that would allow ruminants to become more resilient to the environmental and physiological challenges that they will have to endure during their productive career. As the demand of ruminant products from the rapidly growing human world population is ever-increasing, the aim of this review is to present animal and veterinary scientists as well as nutritionists a multidisciplinary approach towards a sustainable ruminant production, while improving their nutrient utilization, health and welfare, and mitigation of their carbon footprint at the same time. Graphical abstsract: Core competencies required to develop nutritional strategies to sustain lifetime performance in ruminants. Highlights: Nutritional strategies to promote lifetime performances in ruminants are offered. The role of antioxidant as foundations of immunity and health are presented. The role of skeletal health as framework for lifetime performance is discussed. The importance of nutrient utilization as determinant of herd efficiency is described. The relevance of raising ruminants without antibiotics and mitigating their carbon footprint is presented.